Multi‐criteria decision analysis applied to harmful algal bloom management: A case study. (4th February 2017) - Pang, Chengfang; Radomyski, Artur; Subramanian, Vrishali; Nadimi‐Goki, Mandana; Marcomini, Antonio; Linkov, Igor
ABSTRACT: Harmful algal blooms (HABs) have received greater attention in recent years due to an increase in the frequency of outbreaks and a growing potential for blooms to exact considerable economic losses and negatively impact ecosystem health. Human activity has been shown to intensify HAB outbreaks through increased eutrophication, elevated local air and water temperatures, disturbance of the thermal stratification of lakes, and modification of local hydrology. With the advent of new remediation technologies and a better understanding of the ecological factors affecting HABs, mitigating the adverse effects of HABs has become more feasible than ever before but still requires balancing mitigation efficiency, environmental impacts, costs, and stakeholder needs. In the present paper, we discuss potential HAB management solutions and propose using a Multi‐Criteria Decision Analysis (MCDA) framework to analyze the perspectives and priorities of various stakeholders as they pertain to 4 major considerations for HAB mitigation: human health, environmental impact, social impact, and technical feasibility. A hypothetical case study of an HAB‐affected lake is used to demonstrate how stakeholders may prioritize HAB management alternatives within the MCDA framework. Integr Environ Assess Manag 2017;13:631–639. © 2016 SETAC Key Points: Management of harmful algal blooms (HABs) is complex, and trade‐offs are difficult to make. Multi‐Criteria Decision Analysis (MCDA) provides an efficient way to assess management alternatives. Multi‐Criteria Decision Analysis models can provide the basis for uncertainty and sensitivity analysis associated with HAB management. Multi‐Criteria Decision Analysis can be used to assess emerging technologies, including nanotechnology.